Avaliação "in vitro" e "in vivo" da atividade antioxidante do extrato hidroetanólico de folhas de Turnera ulmifolia Linn. var. elegans (Turneraceae) - Brito, Naira Josele Neves de (2009)
Recently, it has been a increasing interest in the antioxidative role of natural products to aid the endogenous protective biological systems against the deleterious effects of oxygen (ROS) and nitrogen (RNS) reactive species. Many antioxidant compounds, naturally occurring from plant sources. Natural antioxidants can protect and prevent the human body from oxidative stress and retard the progress of many diseases in which free radical are involved. Several plants used in the folk medicine to treat certain disorders that are accompanied by inflammation and other pharmacological properties have been proved their attributed properties, such antioxidant activity. Turnera ulmifolia Linn. var. elegans (Turneraceae), frequently employed by population as a medicinal plant, demonstrated antioxidant activity by in vitro and in vivo assays, using its leaf hydroethanolic extract (10%) he in vitro DPPH radical-scanvenging activity showed a strong antioxidant activity (86.57% ± 0.14), similar to Carduus marianus and catequine effects. For the in vivo assays, adult female Wistar rats (n=48) with carbon tetrachloride hepatic injury induced (2,5mL/kg i.p.) were used, Six groups or rats were uses (n=8) [G1 = control (1,25 mL/kg i.p. vehicle); G2 = CCl4 (2,5 mL/kg i.p.); G3 = CCl4 + extract 7 days (500 mg/kg p.o.); G4 = CCl4 + Legalon® 7 days (50 mg/kg p.o.), G5 = CCl4 + extract 21 days (500 mg/kg p.o.) e G6 = CCl4 + Legalon® 21 days (50 mg/kg p.o.)]. The hepatic oxidative injury was evaluated through biochemical parameters [alanine amino transferase (ALT), aspartate amino transferase (AST)] histopathological study, while thiobarbituric acid reactive products (TBAR), glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) levels were used to evaluate proantioxidant parameters. The plant extract tested was found effective as hepatoprotective as evidenced by a decreasing in the ALT and AST activities (p<0.001) and TBAR (plasma, p<0.001 and liver, p<0.001). Levels of GSH (blood, p<0.001 and liver, p<0.001) and antioxidant enzymes [CAT erythrocyte (p<0.05) and hepatic (p<0.01); SOD erythrocyte (p<0.001) and hepatic (p<0.001); GPx erythrocyte (p<0.001) and hepatic (p<0.001)] were also significantly increased. Histopathological changes induced by CCl4 were significantly reduced by the extract treatment. The data obtained were comparable to that of Legalon®, a reference hepatoprotective drug. The results showed that T. ulmifolia leaf extract protects against CCl4 induced oxidative damage. Therefore, this effect must be associated to its antioxidant activity, attributed to the phenolic compounds, present in these extract, which can act as free radical scavengers